2021
DOI: 10.3390/genes12111817
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Phenotypic Landscape of PRPH2-Associated Retinal Dystrophy in Japan

Abstract: Peripherin-2 (PRPH2) is one of the causative genes of inherited retinal dystrophy. While the gene is relatively common in Caucasians, reports from Asian ethnicities are limited. In the present study, we report 40 Japanese patients from 30 families with PRPH2-associated retinal dystrophy. We identified 17 distinct pathogenic or likely pathogenic variants using next-generation sequencing. Variants p.R142W and p.V200E were relatively common in the cohort. The age of onset was generally in the 40’s; however, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
4
9
0
Order By: Relevance
“…Our cohort included 14 females and 14 males. The age of the patients ranged from 37 to 79 years with a mean (±SD) of 58 ± 1235 and the mean age of onset of symptoms was 41 ± 1283 years old, similar to data already reported in previous studies [ 7 , 9 , 20 ]. BCVA of the patients ranged from light perception to 20/20 Snellen.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Our cohort included 14 females and 14 males. The age of the patients ranged from 37 to 79 years with a mean (±SD) of 58 ± 1235 and the mean age of onset of symptoms was 41 ± 1283 years old, similar to data already reported in previous studies [ 7 , 9 , 20 ]. BCVA of the patients ranged from light perception to 20/20 Snellen.…”
Section: Resultssupporting
confidence: 86%
“…An unusual feature already discussed and reported in the literature [ 20 , 30 , 31 ] was the presence of monocular CNV in five affected patients (17%) in our group presenting with different phenotypes (PD, CACD, ECA).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Here, we have demonstrated the clinical features associated with eleven patients who harbor the P210R mutation in PRPH2 . Recently, Oishi et al 39 reported that the missense mutation P210R causes autosomal dominant RP. 15 This clinical diagnosis was likely based on the observation of pigment clumping that occasionally occurs in these patients (see Fig.…”
Section: Discussionmentioning
confidence: 99%